Yaw Moment Compensation by Actuator-Based Control of Brake System in Automobiles. Issue 1 (July 2021) - Bisht, Vaibhav; Saravanakumar, D; Sakthivel, G; Sivakumar, R
Abstract: The growing use of brake systems in enhancing vehicle performance along with safety has promised a greater class of innovation. The presented research first discusses a vehicle dynamics model that accounts for the longitudinal and lateral forces acting on the wheels to compute the yaw moment acting on the vehicle based on the steering angle. Dynamic load transfer due to combined action of gravitational load, gyroscopic couple and centripetal force for real-time behavior is considered in the vehicle dynamics model. With a difference in theory and practice, work then focuses on the various disturbances that affect the dynamics of any vehicle under yawing action. The effect of wind disturbance is considered in-depth for the research and other factors like undesirable tire behavior have been discussed as well. For yaw moment compensation, a unique brake system layout with two circuits (primary & secondary), making the use of shuttle valves has been devised and a closed-loop control system is implemented. Each wheel is autonomously provided a brake force by an electromechanical actuator, computed by its respective PID controller to compensate for the variation in yaw moment caused due to external disturbances.